Sox9-induced chondrogenesis in mesenchymal stem cells was mediated by ERK5 signal pathway - Wang, C; Zhang, T; Liu, W; Meng, H; Song, Y; Wang, W (Cellular and Molecular Biology, 2016)
Sox9 is a member of the high-mobility-group (HMG) box protein superfamily, which is expressed predominantly among cells in mesenchymal condensations during the early development of embryonic skeletons. The extracellular-signal-regulated kinase 5 (ERK5) is one of the mitogen-activated protein kinase (MAPK) family members of protein kinases. Roles for ERK5 signaling in the regulation of chondrogenesis and adult chondrocyte homeostasis have yet to be demonstrated. In this study, we found that ERK5 could down-regulate Col2al and Sox9 expression, and this down-regulation was inhibited by MEK5Î², one of ERK5 inhibitor. Furthermore, we characterized the ERK5 response with the chromatin binding profile of Sox9 in MSCs in a genome-wide manner through an analysis of ChIP-seq data. This study will help to understand the interaction between the ERK5 and Sox9, and facilitate to decipher the mechanism of chondrogenesis in mesenchymal stem cells.